Pengaruh Struktur Aset, Ukuran Perusahaan dan Pertumbuhan Penjualan terhadap Struktur Modal dan Profitabilitas sebagai Variabel Moderasi pada Perusahaan Sektor Pertambangan yang Listing di Bursa Efek Indonesia Periode 2017-2021 - Nuriyaningsih Lubis; Muhammad Arief (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine the effect of asset structure, company size, sales growth on capital structure and profitability as moderating variables in mining sector companies listed on the Indonesia Stock Exchange in 2017-2021. The total population in this study were 46 companies and the sample in this study was 17 companies with 5 years of research and a total of 85 data were obtained. The analysis technique used is Moderated Regression Analysis (MRA). The results showed that the asset structure had no effect on the capital structure. Firm size has no effect on capital structure. Sales growth affects the capital structure. Profitability affects the capital structure. Profitability does not moderate the influence between asset structure and capital structure. Profitability does not moderate the effect of firm size and capital structure. Profitability does not moderate the influence between sales growth and capital structure.